Mumbai International Cruise Terminal - Ghosh, Ayan (2023)
In 1970, a new passenger berth was commissioned at the Ballard Pier Extension for luxury liners. It currently serves as the Mumbai International Cruise Terminal, expected to be commissioned by July 2024. The terminal will have a capacity of handling 200 ships and 10 lakh passengers per annum. Two cruise ships will be able to berth at a time at the dock.